Group portrait of the attendees of the 1949 State Ladies Auxiliary meeting - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the State Ladies Auxiliary, a part of the California Master Plumbers convention, held May 2-4, 1949 in San Jose, California. The group is assembled out of doors in front of the San Jose Civic Auditorium.